2017
DOI: 10.1080/07294360.2017.1325351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating academic development in the higher education sector: academic developers’ reflections on using a toolkit resource

Abstract: The professionalisation of teaching is of increasing importance in United Kingdom higher education due to a number of converging processes including the ongoing proliferation of managerialism, increasing quality agendas and changes to student fee structures. These changes have brought into sharp relief the need for greater understanding of how quality teaching evolves in university settings. One key element of this involves academic development and its impacts on teaching and learning. Current literature in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…Encouragingly, the studies found that academic development was reacted to positively and enhanced relevant learning. However, most evaluation relied solely on qualitative data, and although this approach can capture rich aspects of training participants' experience (Winter et al, 2017), evaluation of change is arguably more validly and reliably assessed via quantitative methods (Rosnow & Rosenthal, 1997). In addition, none of the studies reviewed examined higher education staff development that was focused on academic integrity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Encouragingly, the studies found that academic development was reacted to positively and enhanced relevant learning. However, most evaluation relied solely on qualitative data, and although this approach can capture rich aspects of training participants' experience (Winter et al, 2017), evaluation of change is arguably more validly and reliably assessed via quantitative methods (Rosnow & Rosenthal, 1997). In addition, none of the studies reviewed examined higher education staff development that was focused on academic integrity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Evaluation is a key stage in all teaching-learning processes (Winter, Turner, Spowart, Muneer, & Kneale, 2017). Lecture evaluation is a process of populating information to assess the process and outcome of lectures in order to make policy to improve their quality.…”
Section: Results and Discussion Web-based Lecture Evaluation Systemmentioning
confidence: 99%
“…This more intense competition has motivated an escalation of the entry and promotion requirements (Cadez et al, 2017;Chou & Chan, 2016;Li, 2016;Page, 2020;J. Smith, 2017;Winter et al, 2017). Numerous indicators measuring teaching and research quality have been established.…”
Section: Introductionmentioning
confidence: 99%